The Effect of Passively Viewing a Consent Campaign Video on Attitudes Toward Rape - Rowe, Ellie M.; Hills, Peter J. (Frontiers in Psychology, 2020)
Around 90% of rape victims know their perpetrator making acquaintance rape the most common form of rape, contradicting societal beliefs. There is ambiguity about the meaning and use of consent in sexual scenarios (Beres, 2007). This study used a mixed methods approach to test the effectiveness of a campaign video aimed at increasing understanding of consent. We assessed whether it affected rape judgements in vignettes depicting consensual or non-consensual sexual scenarios. We also manipulated whether making consent the primary or secondary question influenced attitudes. Text responses were also obtained to gain an insight into participant’s reasoning. The campaign showed no significant increase in rape judgements. Making consent primary in question order did lead to greater accuracy in rape judgement. A content analysis of the free-text responses indicated that the presence of the campaign actually reduced people’s use of consent in explaining why a scenario may represent rape: instead they focused on the attractiveness of the attacker. These results are discussed in relation to the effectiveness of passively-viewing campaign material.